(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Numerous retrospective studies have been conducted to analyze the consequences of COVID-19 in pregnant women for their newborns [9]. It is known that vertical transmission of SARS-CoV-2 is possible, but appears to occur in a minority of maternal coronavirus infections during the third trimester [4,5]. Vertical transmission of the novel coronavirus infection (COVID-19) from mother to child is considered to be extremely unlikely [1]. Only a few, and rather controversial, cases of possible vertical transmission have been described in China [2,6] and Peru [3]. According to the current WHO guidelines, COVID-19 tests should be performed using reverse transcription polymerase chain reaction (RT-PCR) as the most accurate and reliable method for diagnosing viral infections [4].